SUPPLY CHAIN PERFORMANCE AND BUSINESS SUSTAINABILITY (Study at 212 Mart Batan Indah-Tangsel) - Tukhas Shilul Imaroh; Katri Widiyani (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The condition of economic development in Indonesia cannot be separated from the role of industry and MSMEs from various regions scattered throughout Indonesia. In the era of global competition, MSMEs face various obstacles such as difficulty in competing, difficulty in obtaining access to capital, inadequate marketing, lack of superior resources, lack of access to suppliers, emergence of new competitors, and no plans to deal with the unexpected. This issue belongs to supply chain management. As one of the MSME forums, the presence of the Sharia Cooperative 212, namely the National Primary Cooperative, was established by Muslim leaders to implement the spirit of Action 212 which is full of brotherhood and togetherness. This spirit is then manifested in efforts to make the Sharia Cooperative 212 as a forum for economic struggle to achieve the economic independence of the people. The purpose of this study was to determine the effect of information sharing, long-term relationships, and process integration on MSME supply chain performance and Business Sustainability. This study uses a survey method by distributing questionnaires, which are measured based on the expectations of business actors. The questionnaire used a Likert scale and Partial Least Square (PLS) analysis. The results of this study indicate that the long term relationship has a positive and significant effect on the performance of the MSME supply chain. Information sharing has a negative and significant effect on MSME supply chain performance. Process integration has a positive and significant impact on MSME supply chain performance. MSME supply chain performance has a positive and significant impact on Business Sustainability. Long term relationship significantly affects Business Sustainability through MSME supply chain performance. Information sharing does not significantly affect Business Sustainability through MSME supply chain performance. And Long term relationship has a significant.